The Study of Factors Affecting the Job Performance of Nurses Working in Selected Teaching Hospitals in Tehran - Vahid Saberzadeh; Javad Abdollahinia; Pedram NourizadehTehrani; Hadi Asheghi; Khatereh Khanjankhani (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Undoubtedly, one of the most important objectives of any organization is to provide high quality and desirable goods and services that depend on the performance of human force of the organization. The performance of physicians and nurses is a very important factor in establishing and enhancing the effectiveness of services. Since nurses are the most fundamental medical staff of the hospital, the present study was performed with the aim of investigating the factors affecting the job performance of nurses working in selected teaching hospitals in Tehran in 2018. Methods: The target group of this study included nurses working in inpatient wards of hospitals, of whom 354 individuals were selected by simple random sampling method. The intraorganizational environment questionnaire (Weisbord), five personality traits (NEO personality inventory), and Paterson's job performance questionnaire were the three data collection tools. The study was conducted in 2018 and the data were analyzed by SPSS20 software using descriptive statistics and artificial neural networks. Results: In the personality traits questionnaire, neuroticism (40.22 ± 6.66) dimension had the highest and responsibility (23.94 ± 4.91) dimension had the lowest mean scores. Also in the inter-organizational environment questionnaire, communication (14.66 ± 4.52) dimension and rewards (21.33 ± 6.54) dimension had the best and worst status, respectively. Comparison of significance coefficients in neural networks showed that dimensions of agreeability (100 %) and marital status (8 %) had the highest and lowest importance in nurses' job performance. Conclusion: The results reveal that the dimensions of personality traits and job agreeability dimension have the most effect on the employees' job performance. Hence, it is possible to improve staff performance by hiring people consistent with their work.